Prostate fiducial marker detection with the use of multi-parametric magnetic resonance imaging. (January 2017) - Dinis Fernandes, Catarina; Dinh, Cuong V.; Steggerda, Marcel J.; ter Beek, Leon C.; Smolic, Milena; van Buuren, Laurens D.; Pos, Floris J.; van der Heide, Uulke A.
Abstract: Background and purpose: The introduction of a magnetic resonance (MR)-only workflow in radiotherapy requires that fiducial markers, used for position verification, can be detected on MR images. Here we evaluate a model for marker detection in prostate cancer patients by combining information from our hospital standard multi-parametric (mp-) MRI protocol (T1-weighted – T1w, T2-weighted – T2w, B0 ) with dedicated sequences (balanced steady-state free precession sequence – bTFE, susceptibility weighted imaging – SWI). Materials and methods: Thirty two patients scheduled for external-beam radiotherapy received a mp-MRI and computed-tomography; the latter was used as ground truth location of the markers. A logistic regression model was implemented for marker detection by combining features from all imaging sequences. The performance of the individual and combined sequences was assessed by determining true and false positive detections. Results: The combination of different sequences (mp-MRI) resulted in a better performance than the best imaging sequence alone (bTFE). Combining mp-MRI + bTFE resulted in good accuracy and a true positive detection rate of 0.94. Conclusions: The standard mp-MRI provides valuable information to detect fiducial markers. The combination of different sequences outperforms the use of a single dedicated sequence. We recommend the addition of a bTFE to the standard mp-MRI protocol to improve fiducial marker detection.